Long‐term outcome of robotic‐assisted laparoscopic rectopexy for full‐thickness rectal prolapse in elderly patients. (March 2014) - Germain, A.; Perrenot, C.; Scherrer, M.‐L.; Ayav, C.; Brunaud, L.; Ayav, A.; Bresler, L.
Abstract Aim Full‐thickness rectal prolapse is common in the elderly, but there are no particular practice guidelines for its surgical management. We evaluated retrospectively the perioperative and long‐term clinical results and function in elderly and younger patients with complete rectal prolapse after robotic‐assisted laparoscopic rectopexy (RALR). Method Seventy‐seven patients who underwent RALR between 2002 and 2010 were divided into Group A (age < 75 years, n = 59) and Group B (age > 75 years, n = 18). Operative time, intra‐ and postoperative complications, length of hospital stay, short‐term and long‐term outcomes, recurrence rate and degree of satisfaction were evaluated. Results There was no significant difference between the groups regarding operation time, conversion, morbidity or length of hospital stay. At a median follow‐up of 51.8 (5–115) months, there was no difference in the improvement of faecal incontinence, recurrence and the degree of satisfaction. Conclusion Robotic‐assisted laparoscopic rectopexy is safe in patients aged over 75 years and gives similar results to those in patients aged < 75 years.